Psychological Skill Model of Collegiate Athletes in Taiwan. Issue 2 (October 2014) - Lin, Kai; Chou, Tzu-Chin Rejoice
The importance of psychological skills to an athlete is widely recognized. The Athletic Psychological Skills Inventory (APSI) was developed to evaluate psychological skills in the Taiwanese sports environment. This study employed the APSI model to refine the psychological skill factor structure. The model was supported as a reliable and valid form of measurement. A second-order confirmatory factor analysis (CFA) confirmed the factor structure of the APSI in Taiwanese collegiate athletes. Peaking under pressure and coping with adversity were combined into a simplified factor, coping with adversity.